2015
DOI: 10.1152/ajpgi.00244.2015
|View full text |Cite
|
Sign up to set email alerts
|

Nkx2.2 is expressed in a subset of enteroendocrine cells with expanded lineage potential

Abstract: There are two major stem cell populations in the intestinal crypt region that express either Bmi1 or Lgr5; however, it has been shown that other populations in the crypt can regain stemness. In this study, we demonstrate that the transcription factor NK2 homeobox 2 (Nkx2.2) is expressed in enteroendocrine cells located in the villus and crypt of the intestinal epithelium and is coexpressed with the stem cell markers Bmi1 and Lgr5 in a subset of crypt cells. To determine whether Nkx2.2-expressing enteroendocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Adult EE cells have been proposed to have in vivo stem cell potential, although lineage tracing from EE marker genes was not employed (Sei et al, 2011; Van Landeghem et al, 2012). Intriguingly, both Neurog3-Cre (Schonhoff et al, 2004), and Nkx2.2-Cre (Gross et al, 2015) robustly mark adult small intestine EE cells and reveal epithelial lineage traces that include all four small intestinal lineages; however, the use of constitutively active Cre strains did not allow inducible lineage tracing in adult animals so cell interconversion events originating in embryogenesis could not be excluded. Interestingly, other studies have suggested that Neurog3 + cells exclusively contribute to EE lineages without multi-lineage potential (Bjerknes and Cheng, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult EE cells have been proposed to have in vivo stem cell potential, although lineage tracing from EE marker genes was not employed (Sei et al, 2011; Van Landeghem et al, 2012). Intriguingly, both Neurog3-Cre (Schonhoff et al, 2004), and Nkx2.2-Cre (Gross et al, 2015) robustly mark adult small intestine EE cells and reveal epithelial lineage traces that include all four small intestinal lineages; however, the use of constitutively active Cre strains did not allow inducible lineage tracing in adult animals so cell interconversion events originating in embryogenesis could not be excluded. Interestingly, other studies have suggested that Neurog3 + cells exclusively contribute to EE lineages without multi-lineage potential (Bjerknes and Cheng, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There may be substantial overlap between Nkx2.2 + , Prox1 + and Bmi1 + cells, and indeed Nkx2.2 is strongly enriched in our Bmi1-GFP transcriptome. However, Nkx2.2 + ISCs do not appear to be mobilized by injury (Gross et al, 2015), in contrast to that of Prox1 + and Bmi1 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…Post-mitotic enteroendocrine cells have also been reported to have injury-induced stem cell activity 88,92 specifically enteroendocrine subsets marked by neuro-genin3-Cre 93 or Nkx2.2-Cre. 94 Using a Bmi1-GFP knock-in allele to allow Bmi1-expressing cell isolation without relying on Bmi1-CreER-mediated lineage tracing, 30,49 researchers showed that single GFP þ intestinal cells could undergo clonogenic organoid formation indicative of stem cell function. 95 GFP þ cells also had a gene expression signature associated with enteroendocrine cells, indicating that quiescent and regeneration-competent Bmi1-expressing subpopulations might be relatively differentiated enteroendocrine cells.…”
Section: Enteroendocrine Cellsmentioning
confidence: 99%
“…However, many of these +4 quiescent stem cell markers are also expressed in Lgr5+ CBCs raising the question as to whether these +4 quiescent stem cells are actually distinct from the Lgr5+ CBC cell population[44]. In addition to +4 quiescent stem cells, several different secretory and enterocyte progenitors can act as facultative stem cell populations including label-retaining cells (LRCs) expressing Paneth and/or enteroendocrine cell markers[45, 46], delta-like ligand 1 + (Dll1 + ) secretory progenitors [47], Sox9+ progenitor cells [48], enteroendocrine Neurog3+ progenitors [49], intestinal alkaline phosphatase (Alpi1+) enterocyte progenitors [50] and others [5154]. Interestingly, recent functional and transcriptomic analysis has demonstrated that +4 quiescent Hopx+ cells are functionally and molecularly distinct from short-term LRCs, which have properties of either enteroendocrine or Paneth cell secretory progenitors [46].…”
Section: Overview Of Gastrointestinal Biology and Functionmentioning
confidence: 99%